2001
DOI: 10.1007/bf02864867
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone status in protein energy malnutrition in Indian children

Abstract: Thyroid hormonal status was measured in 80 malnourished children of different grades (I-IV) of protein energy malnutrition (PEM). Serum levels of tri-iodo thyronine (T3) , thyroxine (T 4) and thyroid stimulating hormone (TSH) were measured by radioimmunoassay. The results were compared with 20 healthy, age and sex matched controls. Levels of T 3 and T 4 were significantly low in PEM cases whereas TSH levels were similar in PEM cases when compared to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
2
5
1
Order By: Relevance
“…Studies conducted by Abrol P et al , Turkey et al and Das BK et al, also showed similar results. 17,18,21 In contrast to present study, study conducted by Orbak Z et al, found that mean TSH levels of children with PEM were higher as compared to controls, study conducted by Kumar S et al, found that mean TSH levels showed a positive increase with increase in severity of PEM with maximum increase been observed in grade III PEM (One-way ANOVA; p= 0.015). 19,20 Normal TSH levels in children with PEM is possibly due to T 4 undergoing intracellular monodeiodination to form T 3 at pituitary level causing negative feedback inhibition of secretion of TSH, central unresponsiveness to low T 3 levels due to low intracellular receptor capacity.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Studies conducted by Abrol P et al , Turkey et al and Das BK et al, also showed similar results. 17,18,21 In contrast to present study, study conducted by Orbak Z et al, found that mean TSH levels of children with PEM were higher as compared to controls, study conducted by Kumar S et al, found that mean TSH levels showed a positive increase with increase in severity of PEM with maximum increase been observed in grade III PEM (One-way ANOVA; p= 0.015). 19,20 Normal TSH levels in children with PEM is possibly due to T 4 undergoing intracellular monodeiodination to form T 3 at pituitary level causing negative feedback inhibition of secretion of TSH, central unresponsiveness to low T 3 levels due to low intracellular receptor capacity.…”
Section: Discussioncontrasting
confidence: 89%
“…Studies conducted by Abrol P et al and Turkey et al have showed similar results ( Table 6, Table 7). 17,18 Similar results are reported by study done by Kumar S et al, Orbak Z et al and study conducted by Das BK et al, found that mean T 3 levels was significantly lower in malnourished children as compared to controls, however in their study they found no significant difference in mean T 4 levels of cases and controls. [19][20][21] Low T 3 levels in children with PEM is probably due to low binding proteins, impaired thyroxine monodeiodination in liver which leads to decreased peripheral conversion of T 4 to T 3 and elevated corticosteroids which is often seen in children with malnutrition (acts by inhibiting 5' deiodinase system) and low T 4 levels in children with PEM can be due to fall in thyroid secretion rate, depletion of reserves and failure of the adaptive mechanism.…”
Section: Discussionsupporting
confidence: 77%
“…The levels decreases as the severity of malnutrition increases and the difference between the TSH levels among cases with moderate and severe malnutrition was statistically significant (p <0.001). (16) The result disagreed with another result done by Abrol et al and Turkay et al, in their study found no significant difference in TSH when PEM children were compared to healthy controls (17) (18) The result disagreed with another result which finding confirmed that, TSH levels were similar in both groups (malnourished children and control group). (19) Also this result disagreed with another result which showed that, TSH levels were similar in PEM cases when compared to controls.…”
Section: Male 50%mentioning
confidence: 82%
“…14 Abrol P et al, Mean T3, T4 and TSH levels in PEM group was 107.7, 8.3 and 2.6 respectively, which were higher than the mean values of the present study. 6 This could be substantiated by the fact that severity of malnutrition is higher in Madhya Pradesh in comparison to other Indian states.…”
Section: Discussionmentioning
confidence: 99%